Governance-Based Library Management, More Effective and Efficient - Majid, Ivan Kurnia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
This study was conducted to determine how implementation of management in the activities of the package service program. Management in question is how to implement management functions such as planning, organizing, staffing, directing, budgeting, and monitoring. This research is a descriptive research with a qualitative approach. Data collection techniques in this study were through interviews, observation, and literature review. The results or data obtained are analyzed using three stages, namely data reduction, then the data is presented in the form of narrative text and draws conclusions according to the problem formulation that has been described. The results of the study indicate that in running the program, the package service has implemented management functions. Activities related to planning are carefully arranged, the stages of activities, a series of times are aligned. Implementation in activities by grouping activities, division of labor and providing direct directions is also implemented so that it goes according to plan even though limited transportation facilities hinder the delivery of package services to the locations of the fostered libraries. Meanwhile, for coaching activities now no longer use the budget. Supervision is carried out by going directly to the target library, but the time to supervise the assisted library in the Jakarta area is still not on schedule.